Employment problems in western Europe's industrial states - Heinz Werner (Intereconomics, 1977)
Until the start of the seventies the situation on the labour markets of the European industrial states was considered with relative optimism. The high growth rates which most of the countries had achieved seemed to be sufficient to absorb the increases in the available labour force. The author discusses the changed situation and its consequences.
Keywords: 330; Labour Markets